Pengaruh Kewajiban Penyediaan Modal Minimum dan Non-Performing Financing Terhadap Cadangan Kerugian Penurunan Nilai Pada PT. Bank KB Bukopin Syariah - Setiawan , Dimas; Ibrahim, Zaini; Wulandari, Soliyah (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2024)
The study aims to determine the effect of Minimum Capital Provision Obligations on Impairment Loss Reserves, the effect of Non-Performing Financing on Impairment Loss Reserves, and the simultaneous effect of Minimum Capital Provision Obligations and Non-Performing Financing on Impairment Loss Reserves. Research in the form of secondary data on quarterly financial statements for 2015-2022, data collection techniques, literature studies, and documentation techniques. Research sample at PT. Bank KB Bukopin Syariah, purposive sampling method sampling technique. Multiple linear regression analysis research methods: normality test, multicollinearity, autocorrelation, heteroscedasticity, descriptive statistics, t test, F test, correlation coefficient, and determination coefficient. Partial conclusion, Minimum Capital Provision Obligation has no effect on Impairment Loss Reserves based on sig. value 0.09 > 0.05, while Non-Performing Financing has a positive and significant effect on Impairment Loss Reserves based on sig. value 0.00 < 0.05. Simultaneous conclusion, Minimum Capital Provision Obligation and Non-Performing Financing affect Impairment Loss Reserve with a value of sig. 0.00 < 0.05. R value of 0.85% means that Minimum Capital Provision Obligations and Non-Performing Financing against Impairment Loss Reserves have a very strong relationship. The R2 value of 70.1% means that the Impairment Loss Reserve is influenced by Minimum Capital Provision Obligations and Non-Performing Financing, and the remaining 29.9% is influenced by other variables.